The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4049/jimmunol.1200649
|View full text |Cite
|
Sign up to set email alerts
|

Lyn Signaling To Upregulate GANP Is Critical for the Survival of High-Affinity B Cells in Germinal Centers of Lymphoid Organs

Abstract: Signals through BCR and costimulatory molecules play essential roles in selecting high-affinity B cells with Ig V-region mutations in the germinal centers (GCs) of peripheral lymphoid organs. Lyn-deficient (lyn−/−) mice show impaired BCR signal triggering for cell proliferation and GC formation, causing hyper-IgM, and display autoimmunity after aging. In this study, we demonstrate that Lyn-mediated signaling to upregulate GANP is essential for the survival of mature GC-like (mGC) B cells with high-affinity typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Recently, it has gradually been revealed that GANP possesses multiple functions. Previous report indicated that GANP upregulation is essential for the survival of mature germinal center B-cells with high affinity type due to suppression of DNA damages [9]. Taken together with the previous and present results, GANP may also be required for the survival of HRS cells originated from germinal center B-cells of lg-ganp Tg mice.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Recently, it has gradually been revealed that GANP possesses multiple functions. Previous report indicated that GANP upregulation is essential for the survival of mature germinal center B-cells with high affinity type due to suppression of DNA damages [9]. Taken together with the previous and present results, GANP may also be required for the survival of HRS cells originated from germinal center B-cells of lg-ganp Tg mice.…”
Section: Discussionsupporting
confidence: 90%
“…Our study suggests that GANP plays an important role in the transdifferentiation or reprograming of B cells to macrophage-like cells and the consequent development of B-cell/macrophage biphenotypic Hodgkinoid lymphoma that corresponds to human HL. Our previous report indicated that GANP, one of the targets of Lyn-mediated signaling, is most likely regulated via the PU.1 binding site of the ganp promoter region [9,17]. Because PU.1 exerts shared transcriptional regulation of both B-cell and macrophage differentiation [18,19], PU.1 may modulate the dynamic reprogramming between B-cell and macrophage differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of dasatinib in reducing the splenic follicle size (Fig. 3E) prompted an investigation of germinal center (GC) cells, a rapidly proliferating population of B cells that is dependent on Lyn kinase signaling [35][37]. We found that dasatinib caused a significant reduction of B220 + cells expressing the GC markers CD95 and GL7 (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…6B-6D). The effect of dasatinib on germinal center (GC) B cells was also examined, since they are highly proliferative and dependent on Lyn kinase signaling [36][37][38]. Dasatinib was associated with a significant reduction of B220 þ cells that express the GC markers CD95 and GL7 (Fig.…”
Section: Dasatinib Targets Immature B Cells In the Spleenmentioning
confidence: 99%